A higher‐level classification of the Pannonian and western Pontic steppe grasslands (Central and Eastern Europe). Issue 1 (16th September 2016) - Willner, Wolfgang; Kuzemko, Anna; Dengler, Jürgen; Chytrý, Milan; Bauer, Norbert; Becker, Thomas; Biţă‐Nicolae, Claudia; Botta‐Dukát, Zoltán; Čarni, Andraž; Csiky, János; Igić, Ruzica; Kącki, Zygmunt; et al.
Abstract: Questions: What are the main floristic patterns in the Pannonian and western Pontic steppe grasslands? What are the diagnostic species of the major subdivisions of the class Festuco‐Brometea (temperate Euro‐Siberian dry and semi‐dry grasslands)? Location: Carpathian Basin (E Austria, SE Czech Republic, Slovakia, Hungary, Romania, Slovenia, N Croatia and N Serbia), Ukraine, S Poland and the Bryansk region of W Russia. Methods: We applied a geographically stratified resampling to a large set of relevés containing at least one indicator species of steppe grasslands. The resulting data set of 17 993 relevés was classified using the TWINSPAN algorithm. We identified groups of clusters that corresponded to the class Festuco‐Brometea . After excluding relevés not belonging to our target class, we applied a consensus of three fidelity measures, also taking into account external knowledge, to establish the diagnostic species of the orders of the class. The original TWINSPAN divisions were revised on the basis of these diagnostic species. Results: The TWINSPAN classification revealed soil moisture as the most important environmental factor. Eight out of 16 TWINSPAN groups corresponded to Festuco‐Brometea . A total of 80, 32 and 58 species were accepted as diagnostic for the orders Brometalia erecti, Festucetalia valesiacae and Stipo‐Festucetalia pallentis, respectively. In the further subdivision of the orders, soil conditions, geographic distribution and altitude could be identified as factors driving the major floristic patterns. Conclusions: We propose the following classification of the Festuco‐Brometea in our study area: (1) Brometalia erecti (semi‐dry grasslands) with Scabioso ochroleucae‐Poion angustifoliae (steppe meadows of the forest zone of E Europe) and Cirsio‐Brachypodion pinnati (meadow steppes on deep soils in the forest‐steppe zone of E Central and E Europe); (2) Festucetalia valesiacae (grass steppes) with Festucion valesiacae (grass steppes on less developed soils in the forest‐steppe zone of E Central and E Europe) and Stipion lessingianae (grass steppes in the steppe zone); (3) Stipo‐Festucetalia pallentis (rocky steppes) with Asplenio septentrionalis‐Festucion pallentis (rocky steppes on siliceous and intermediate soils), Bromo‐Festucion pallentis (thermophilous rocky steppes on calcareous soils), Diantho‐Seslerion (dealpine Sesleria caerulea grasslands of the Western Carpathians) and Seslerion rigidae (dealpine Sesleria rigida grasslands of the Romanian Carpathians). Abstract : Our study provides the first broad‐scale classification of the Pannonian and western Pontic steppe grasslands, based on a data set of 17 993 relevés. We introduce a supervised consensus approach to identification of diagnostic species which involves three numerical fidelity measures as well as external expert‐knowledge. The orders Brometalia erecti, Festucetalia valesiacae and Stipo‐Festucetalia pallentis are discussed in detail.